POLA ASUH BALITA IBU-IBU KELOMPOK SASARAN PADA PROGRAM KEGIATAN BINA KELUARGA BALITA USIA 0–12 BULAN DUSUN GANDEKAN KARTASURA - Hastasari, Chatia; Anggitya, Paramastu Titis; Musslifah, Anniez Rachmawati (Universitas Negeri Yogyakarta, 2015)
AbstractThe rapid advancement of information technology was not enough to bring change in the attitude of the mothers in applying good parenting on their children. There are still many women who apply parenting capital only a myth or hereditary habits. The impact of the low level of understanding about parenting maternal age, especially toddlers 0-12 months of this should be a serious concern of all parties concerned, as stem from the application of good parenting toddlers that we can prepare the next generation of quality. The purpose of this study was to determine the parenting toddlers of mother target groups Program BKB aged 0-12 months during which also evaluated from the perspective of communication. This study was designed using a